Effects of the Expanded Panama Canal on Vessel Size and Seaborne Transport - Carral, Luis; Tarrio-Saavedra, Javier; Castro-Santos, Laura; Lamas-Galdo, Isabel; Sabonge, Rodolfo (Promet - Traffic&Transportation, 2018)
The Panama Canal (PC) expansion will have an impact on trading patterns and the manner in which goods are transported around the world. Once the third set of locks at the Canal began their operation, it was clear that the way in which vessels transited the canal and their maximum dimensions were going to change. As such, the expanded Canal will undoubtedly mean that a new kind of vessel will come into existence. In terms of dimensions, these Neopanamax ships will be adapted to how the locks operate. However, this effect will not be the same across the full range of traffic. After the first transit on 26 June 2016, it was possible to obtain access to transit data for Neopanamax ships. A thorough statistical study of these new datasets would involve analysing how these new locks impact the vessel size and seaborne transport.